Peran tegas dan pragmatis Mongolia dalam Kebijakan Connect Central Asia India: Lintasan saat ini dan Masa Depan ke Depan - Kumar, Subhash; Chatterjee, Souvik (Jurusan Ilmu Politik Universitas Bangka Belitung, 2021)
Mongolia’s uniqueness and importance in contemporary world politics lie in its geographical situating, demography, and economy. Geographically landlocked and situated in the Eurasian intersection, Mongolia has the lowest population density of any sovereign country on the planet. Sandwiched among Russia and China Mongolia's harsh environment limit its economic interests. However, Mongolia's geostrategic position, unexplored energy assets, and democratic governance have expanded its importance in global politics. Because of such Mongolia holds a key position in India's Act East and Connect Central Policy to counter China's expansionist policies in North-East Asia. With regards to India-Mongolia relations, the two nations share a rich historical legacy. Tibetan Buddhism the most prevailing religion in Mongolia makes social linkages, Democracy solidified further connections between India and Mongolia. Because of these old and profoundly established linkages, India-Mongolia are 'spiritual neighbors'. However, China still has an overreaching control over Mongolia’s trade, commerce, and other sectors. China also dominates intra-regional trade in North-East Asia. Under India’s Connect Central Asia India attempts to counter Chinese encirclement by delving into close strategic, economic, and energy relations with China's neighbors like Mongolia and CAS. However, the achievement or failure of India's Connect Asia Policy will depend upon India's political as well as its diplomatic will to transform India's interest in regional integration in reality.